1986
DOI: 10.1038/bjc.1986.259
|View full text |Cite
|
Sign up to set email alerts
|

Tumour marker antigen CA125 in pancreatic cancer: A comparison with CA19-9 and CEA

Abstract: Summary CA125 is a tumour marker test based on a monoclonal antibody against an antigen from an ovarian carcinoma cell line. Serum concentrations of CA125 were determined in 95 patients with pancreatic cancer and in 106 patients with benign pancreatic, biliary and hepatocellular diseases. The CA125 concentrations were compared with the CA19-9 and CEA levels. Almost half (45%) of the patients with pancreatic cancer had an elevated CA125 level (>35Uml-1). Elevated values were also found in benign diseases (24%),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
44
1

Year Published

1988
1988
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(48 citation statements)
references
References 11 publications
3
44
1
Order By: Relevance
“…Several other sources of CA125 are likely -50% of patients with poorly differentiated pancreatic tumours have high serum levels of CA125 (Haglund, 1986) whereas our study suggests that such tumours express the antigen at a very low level.…”
contrasting
confidence: 47%
See 1 more Smart Citation
“…Several other sources of CA125 are likely -50% of patients with poorly differentiated pancreatic tumours have high serum levels of CA125 (Haglund, 1986) whereas our study suggests that such tumours express the antigen at a very low level.…”
contrasting
confidence: 47%
“…CA125 was originally identified as a marker of non-mucinous ovarian tumours but elevated serum levels have been found in patients with gastrointestinal malignancy (Klug et al, 1984). Haglund (1986), found raised serum levels of CA125 in 45% of patients with pancreatic cancer and in 24% of patients with benign pancreatic disease but was unable to identify the source of CA125. In our study, the expression of CA125 in tissue sections of pancreatic cancer and chronic pancreatitis has been assessed by an immunohistochemical method.…”
mentioning
confidence: 99%
“…Mesothelin binds to the mucin 16 antigen (8), which is also overexpressed in pancreatic and ovarian cancers (9,10). Although many studies have examined the possible function of mesothelin, its role in cancer is still unclear and may be cancer-type specific (11).…”
Section: Introductionmentioning
confidence: 99%
“…The most successful of these has proved to be CA19-9, which recognises the sialylated blood group Lewis antigen, which is expressed on a mucin secreted by the pancreatic tumour into the serum (Magnani et al, 1983). However, most published studies have shown a considerable overlap between CA19-9 serum levels in pancreatic cancer and controls (Haglund et al, 1986;Savarino et al, 1984;Tatsuta et al, 1985;Harmenberg et al, 1988). It contain the high molecular weight abnormal glycoprotein was performed and 100,lp of these diluted samples applied in duplicate to coat micro-ELISA plates for 16h at 4°C.…”
mentioning
confidence: 99%
“…These include carcinoembryonic antigen (CEA) (Gold & Freedman, 1965;Tatsuta et al, 1984), pancreatic oncofetal antigen (POA) (Banwo et al, 1974;Nishida et al, 1985), pancreatic cancer associated antigen (PCAA) (Chu et al, 1977;Loor et al, 1984), (Metzgar et al, 1984;Sawaku et al, 1986), CA19-9 (Koprowski et al, 1979;Haglund et al, 1986b), CA50 (Lindholm et al, 1983;Habib et al, 1986) and CA12-5 (Lehmann et al, 1984;Haglund, 1986). The most successful of these has proved to be CA19-9, which recognises the sialylated blood group Lewis antigen, which is expressed on a mucin secreted by the pancreatic tumour into the serum (Magnani et al, 1983).…”
mentioning
confidence: 99%